DESCRIBE REASONING OF STUDENTS IN COMPLETING THREE-DIMENSIONAL PROBLEM-SOLVING - N. Nisraeni; Dwi Risky Arifanti (Universitas Sembilanbelas November Kolaka, 2018)
This study aims to describe reasoning by highly capable subjects (ST), medium-impacted subjects (SS), and low-ability subjects (SR) in completing three-dimensional problem-solving tasks. This research is a qualitative descriptive research. Instruments in this study are researchers as the main instrument guided by the task of solving problems Mathematics and interview guidelines are valid. The subjects of this study were students of class XI IPA C consisting of 3 people (high-ability subject (ST), medium-skilled subjects (SS), and low-ability subjects (SR)). The research process follows the steps of: (a) formulating the reasoning indicator in solving Mathematics problem, (b) formulating the supporting instrument (valid problem solving task of Mathematics and interviewing), (c) did research subject taking, (d) perform data retrieval to uncover students' reasoning in Mathematical problem solving, (e) do triangulation techniques to obtain valid data Â (f) perform analysis of student reasoning data in problem solving, (g) conduct discussion of result of analysis, (h) make a conclusion of research result. The results of a highly capable subject study show: 1) in understanding the problem using inductive reasoning type analogies, 2) planning completion using inductive reasoning, 3) carrying out the settlement plan using inductive and deductive reasoning, 4) re-examining using common procedures. While for the subject of moderate ability and low-ability subjects in solving problems only meet one reasoning indicator that is filed allegations (inductive type of analogy) is at the stage of understanding the problem. By looking at the students' abilities teachers need to provide non-routine questions so that students are better trained in reasoning and able to develop students' communication skills both in the learning process and in the community environment.